Respuesta :

Answer:

Solution to the given expression is [tex](x^2 -10y^2 -2xy)[/tex]

Step-by-step explanation:

Here, the given expression are:

[tex]P(x) = 2x^2- 3xy+4y^2\\Q(x) = 3x^2 - 5xy-6y^2[/tex]

To Solve for : Q(x)  - P(x)

Now substitute the value of P(x) and Q(x) , we get:

[tex]Q(x) - P(x) = P(x) = (3x^2 - 5xy-6y^2) - (2x^2- 3xy+4y^2)\\= 3x^2 - 5xy-6y^2 - 2x^2+3xy-4y^2\\=x^2-10y^2-2xy\\\implies Q(x) - P(x) = (x^2-10y^2-2xy)[/tex]

Hence solution to the given expression is [tex](x^2 -10y^2 -2xy)[/tex]

ACCESS MORE